IN A WORLD OF THEIR OWN: MEMORY AND IDENTITY IN THE FISHING SONGS OF A MIGRANT EWE COMMUNITY IN GHANA - Otchere, Eric Debrah (International Library of African Music, 2017)
The musical traditions of the southern Ewe of Ghana; particularly the Anlo, have been subject to a substantial amount of research. Existing research has focused on Anlo musical traditions as practiced in its original context. Comparably little is known about these musical traditions as performed by Anlo migrants living and working among a linguistically and culturally different ethnic group. Furthermore, fishing songs of the Anlo, even at home, have escaped most academic research. In this article, I address both shortcomings by focusing on Anlo fishing songs as performed by a migrant Anlo community living among the Fante in Cape Coast. Employing a variety of qualitative research techniques such as in-depth interviews, participant observation and a two-way inter-subjectivity, I explore the extent to which these fishing songs serve purposes beyond their perceived role of accompanying and easing work. Specifically, I examine how the fishing songs of the migrant Ewe community provide a solid basis for negotiating individual and collective memories and identities.
Keywords: Music; Memory; Anlo (African people); Fanti (African people); Migration; Ewe (African people); Ghana; Identity; Fishermen Songs; African Music